The impact of military work experience on later hiring chances in the civilian labour market: Evidence from a field experiment - Stijn Baert; Pieter Balcaen (Kiel Institute for the World Economy (IfW), 2013)
This study directly assesses the impact of military work experience compared with civilian work experience in similar jobs on the subsequent chances of being hired in the civilian labour market. It does so through a field experiment in the Belgian labour market. A statistical examination of our experimental dataset shows that in general we cannot reject that employers are indifferent to whether job candidates gained their experience in a civilian or a military environment.
Keywords: C93; J45; J24; J71; 330; field experiments; hiring discrimination; economics of defence